Mechanical Properties of Polymer Coatings Applied to Fabric - Serhiy Horiashchenko (Polymers, 2020)
The polymer film, formed on fabric, has a diverse resistance to impact (shear) forces during deformation. An original model of the capillary-porous structure of the fabric, partially filled with polymer, was presented and discussed in this paper. Polymer material fixing relations were developed, taking into account the fabric structure and changes of polymer temperature. Experimental studies were performed on three different materials: artificial leather SK-2, GOST 16119-70 (230 g/m2); genuine beef skin, GOST 939-75 (2.2 g/m3); and fabric denim, GOST 29298-2005 (225 g/m2). The value of mathematical model analysis deviation compared with the experimental value was approximately 12%. The obtained mathematical dependences were the basis for predicting the increase of the dimensional stability of garments by applying hot melt polymer to its surface. It is also possible to design new equipment for its implementation.